2015
DOI: 10.4236/jgis.2015.74033
|View full text |Cite
|
Sign up to set email alerts
|

Social Vulnerability Assessment to Flood in Medina Gounass Dakar

Abstract: This paper is about the assessment of social vulnerability (SV) as a critical component of comprehensive disaster risk assessment. This study was conducted in Medina Gounass Dakar, Senegal, to bring out evidence that flooding was a threat to human security. The aim of this present study is to assess the social vulnerability to flood in Medina Gounass. Survey was carried out using structured questionnaires drawn on one hundred randomly selected households. For vulnerability assessment, the Methods for the Impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
(5 reference statements)
1
15
0
1
Order By: Relevance
“…It has been reported that in the last decade, urban floods have impacted most parts of the world including the USA, Europe, Asia, and Africa [6][7][8][9][10][11][12]. Flooding occurs in the least developed nations as well as in the most developed countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in the last decade, urban floods have impacted most parts of the world including the USA, Europe, Asia, and Africa [6][7][8][9][10][11][12]. Flooding occurs in the least developed nations as well as in the most developed countries [13].…”
Section: Introductionmentioning
confidence: 99%
“…It analyzes the physical, technical, environmental, social, cultural, and institutional vulnerability to a specific hazard and considers countermeasures for improving social and economic resilience. It is a framework of a multidimensional, comprehensive, systematic vulnerability assessment [45][46][47]. It has been reported that the social vulnerability of a group depends on its degree of exposure, sensitivity, and capability to respond to dangerous situations [17,26,47].…”
Section: Move Frameworkmentioning
confidence: 99%
“…Currently, it is widely used in various evaluation studies based on indicators to calculate the total value of a certain evaluation item. For many studies, the value of the evaluation item is calculated using the following formula [17,45]:…”
Section: Calculation Of the Social Vulnerability Of Floodsmentioning
confidence: 99%
“…Generally, vulnerability is defined as the potential for loss when a disaster has occurred (Sané et al, 2015). Flood vulnerability assessment has been studied in several developed countries, yet, in Malaysia, there is limited knowledge of vulnerability in a natural disaster.…”
Section: Literature Reviewmentioning
confidence: 99%